Make America Relevant Again! Teaching American Studies in Denmark - Kasper Grotle Rasmussen (American Studies in Scandinavia)
Danes are pro-American and generally fascinated by the United States, but university students are not flocking to American studies programs in Denmark. During the last five years, enrollment numbers have dropped in the country’s only BA and MA programs in American studies at the University of Southern Denmark, and fewer courses in American topics are offered at other Danish universities. This article presents the American studies teaching landscape in Denmark and zooms in on the BA and MA programs in American studies at the University of Southern Denmark in the city of Odense to analyze the problem of enrollment numbers and suggest a remedy consisting of a greater focus on “Global America” in context, greater focus on solving real-life problems in class, and greater teaching cooperation across the Nordic countries.